When to think about a Lachesis muta envenomation in the Western Brazilian Amazon: Lessons from a case report - Jacqueline de Almeida Gonçalves Sachett; Ana Paula Saboia Marinho; Marizete Melo de Oliveira Santos; Hui Wen Fan; Paulo Sérgio Bernarde; Wuelton Marcelo Monteiro (Revista da Sociedade Brasileira de Medicina Tropical, 2022)
ABSTRACT In the Brazilian Amazon, envenomations by lancehead pit vipers prevail across the region, while bushmaster (Lachesis muta) envenomations are rarely confirmed. Here, we described a moderate snakebite, diagnosed as a lancehead pit viper envenomation upon admission and treated with four vials of Bothrops antivenom. Blood remained unclottable for 4 days of hospitalization. On day 4, after admission, the patient presented pictures of the perpetrating snake to the hospital staff, which was identified as a Lachesis muta specimen. After administering 10 vials of Lachesis antivenom, blood became clottable 12 hours after treatment. The patient was discharged without complaints.